2022
DOI: 10.1007/s10479-021-04485-3
|View full text |Cite
|
Sign up to set email alerts
|

Sourcing decision under interconnected risks: an application of mean–variance preferences approach

Abstract: Supply chains are customarily associated with multiple interconnected risks originated from supply side, demand side, or from the unanticipated background uncertainties faced by a firm. Also, effective functioning of supply chain hinges on sourcing decisions of inputs (raw materials). Therefore, there is a striking need to analyse the risk preference of the decision maker while going for optimal sourcing decision under varying degree of interconnected supply chain risks. This study addresses this issue by anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…, is comparable to the condition that 'index of partial relative prudence' lies below two under the EU-setting (also see Mukherjee & Padhi, 2022).…”
Section: Theoretical Setting-mean Variance Approachmentioning
confidence: 85%
See 3 more Smart Citations
“…, is comparable to the condition that 'index of partial relative prudence' lies below two under the EU-setting (also see Mukherjee & Padhi, 2022).…”
Section: Theoretical Setting-mean Variance Approachmentioning
confidence: 85%
“…iv. Lajeri-Chaherli and Nielsen (2000) and Eichner andWagener (2003, 2005) have demonstrated that Kimball's (1990) Eichner, 2008;Eichner & Wagener, 2009, 2011Epstein, 1985;Guo et al, 2018;Mukherjee & Padhi, 2022;Padhi & Mukherjee, 2021;Ormiston & Schlee, 2001) have established equivalents of the EU properties, such as 'risk vulnerability', 'properness', 'temperance', and so forth in terms of the relative willingness-to-pay for variations in risk. This is within the research scope of U σ, μ ð Þ-analysis.…”
Section: Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the literature recognizes that location plays an important role in diversifying risks of a supply chain and has been recognized as one the remarkable sources of risk in supply chains (Tang and Musa 2011 ; Mukherjee and Padhi 2022 ). Recent studies address this issue by developing analytical models, experimental studies, and survey studies.…”
Section: Discussionmentioning
confidence: 99%